A clinical audit on the utilization of group O-negative red cells and the lesson learnt - Arzina Aziz Ali; Hira Qadir; Areeba Khalid; Bushra Moiz (Asian Journal of Transfusion Science)
BACKGROUND: Ideal blood inventory management involves guaranteeing maximal availability of blood while minimizing wastage. Benchmark for the guidance of O (Rh) D-negative red blood cells (ONEG RBCs) is not widely available. In this study, we aimed to identify the areas of improvement in blood center inventory of ONEG RBCs through a clinical audit. MATERIALS AND METHODS: During April 2017 to March 2018, patients who received ONEG RBCs units were studied for their demographics, primary reason for admission, location, and clinical condition. Data were collected from computerized blood center information system, online integrated laboratory data (Integrated Laboratory Management System), and patients’ medical record charts. Children at ≤18 years were included in the pediatric population as per our institutional criterion while a female between 15 and 49 years was considered as having childbearing potential according to previously published data. RESULTS: Overall, 807 units (2.8%) of ONEG RBCs were transfused during 577 transfusion events with a median (inter quartile range) of 2 (1–3) units per patient in each transfusion event. Recipients of ONEG RBCs were 221 unique patients including 91 females (41%) and 130 males (59%) and only 44 (20%) females had child-bearing potential. Overall, 72 of 807 red cell units (8.9%) were transfused to young females of O/non-O negative/unknown group and were classified as “obligatory.” Neonates, pediatric patients, chronically transfused, and bone marrow transplant recipients received 337 of 807 (42%) units and were marked as “acceptable.” Transfusion of 398/807 units (49%) to females of nonchildbearing potential and adult males could have been saved for those with a mandatory transfusion requirement of ONEG RBCs. CONCLUSIONS: This clinical audit showed that 409 of 807 of ONEG RBCs (51%) were transfused according to the guidelines while 398 of 807 of these (49%) could have been saved for other mandatory requirements. Appropriate policies, planning, education of physicians, and regular clinical audits are needed to bring the desired change in transfusion practices.